Answer:
v = (m₁ –m₂) / (m₁ + m₂) 39.2
Explanation:
For this exercise, let's use Newton's second law, since the mass of the chain is zero has forces. Let's call the block on the left 1 and the one on the right 2
For the block on the left
W₁ - T = m₁ a
For the block on the right
T - W₂ = m₂ a
Where the acceleration (a) is the same for the entire system, so that the chain does not lose tension,
To solve this system of equations let's add it
W₁ - W₂ = (m₁ + m₂) a
a = (m₁ –m₂) / (m₁ + m₂) g
Now we can use the kinematic relationship to find the speed of the block
v = v₀ + a t
v = 0 + (m₁ –m₂) / (m₁ + m₂) g t
We substitute the time t = 4 s
v = (m₁ –m₂) / (m₁ + m₂) 9.8 4
v = (m₁ –m₂) / (m₁ + m₂) 39.2
For a specific value we must have the mass of the blocks